Genome-wide association analysis of self-reported daytime sleepiness identifies 42 loci that suggest biological subtypes - Heming Wang (Nature Portfolio, 2019)
A main symptom of chronic insufficient sleep is excessive daytime sleepiness. Here, Wang et al. report 42 genome-wide significant loci for self-reported daytime sleepiness in 452,071 individuals from the UK Biobank that cluster into two biological subtypes of either sleep propensity or sleep fragmentation.